2007
DOI: 10.1002/ptr.2255
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of the immune functions in aged mice by supplementation with a new herbal composition, HemoHIM

Abstract: The effect of a new herbal composition, HemoHIM, on immune functions was examined in aged mice, in which various immune responses had been impaired. The composition HemoHIM was prepared by adding the ethanol-insoluble fraction to the total water extract of a mixture of three edible herbs, Angelica Radix, Cnidium Rhizoma and Paeonia Radix. Supplementation to the aged mice with HemoHIM restored the proliferative response and cytokine production of splenocytes with a response to ConA. Also, HemoHIM recovered the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 50 publications
4
19
1
Order By: Relevance
“…Consistent with our findings, some reports have shown that aging increases IFN-γ production [30-34]. In contrast, other reports have shown that aging reduces IFN-γ production in mice [35-37], whereas Kovacs et al . reported that IFN-γ production did not differ between young and aged mice with both sham and experimental burn injury [38].…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with our findings, some reports have shown that aging increases IFN-γ production [30-34]. In contrast, other reports have shown that aging reduces IFN-γ production in mice [35-37], whereas Kovacs et al . reported that IFN-γ production did not differ between young and aged mice with both sham and experimental burn injury [38].…”
Section: Discussionsupporting
confidence: 92%
“…Taken together, these data would suggest that lymphocytes from old donors would be impaired in their capacity to stimulate antigen presenting cells to produce certain cytokines such as IL-12 p70, which could result in low cytokine release, including IL-1, by monocyte-macrophages. Indeed, our data and that of others in splenocytes have found decreased ConAstimulated levels of IL-12 p70 and IL-1 in old mice (Khansari and Gustad 1991;Park et al 2008). However, in the present results the very old mice showed increased IL-1α and IL-1β in response to this mitogen.…”
Section: Discussioncontrasting
confidence: 60%
“…13 We also investigated the effect of HemoHIM on a restoration of the immune functions that had been impaired in aged mice. 19 In our previous study, we showed that HemoHIM accelerated the recovery of immune cells in mice treated with cyclophosphamide, which is a well-known chemotherapy agent. 20 Although HemoHIM alone did not directly kill the cancer cells (data not shown), our results showed that HemoHIM administration enhanced the therapeutic efficacy of IR in melanoma-bearing mice.…”
Section: Discussionmentioning
confidence: 96%